MASTERING BLAZOR WEBASSEMBLY a step-by-step guide to developing advanced single-page applications with Blazor WebAssembly - Mozaffar, Ahmad (Packt Publishing Ltd., 2023)
Leverage the power of WebAssembly to develop cutting-edge frontend web applications systematically with this comprehensive guide Purchase of the print or Kindle book includes a free PDF eBook Key Features Explore Blazor WebAssembly through a systematic, step-by-step approach Discover the concepts essential to develop and deploy real-world SPAs Create robust components and develop efficient unit tests by using the bUnit framework Book Description Blazor WebAssembly is a revolutionary technology in software development that enables you to develop web applications with a rich user interface using C# without JavaScript. It can be run natively in the browser and soon on mobile apps with .NET MAUI, making it a superweapon in the .NET developer's toolbox. This capability has opened the doors for the JavaScript community to have a stable framework to build single page applications (SPAs) maintained by Microsoft and driven by the community. Mastering Blazor WebAssembly is a complete resource that teaches you everything you need to build client-side web applications using C# & .NET 7.0. Throughout this book, you'll discover the anatomy of a Blazor WebAssembly project, along with the build, style, and structure of the components. You'll implement forms to catch user input and collect data, as well as explore the topics of navigating between the pages in depth. The chapters will guide you through handling complex scenarios like RenderTrees, writing efficient unit tests, using variant security methods, and publishing the app to different providers, all in a practical manner. By the end of this book, you'll have the skills necessary to build web apps with Blazor WebAssembly, along with the basics for a future in mobile development with .NET MAUI and Blazor. What you will learn Develop basic and advanced components in Blazor to meet your application's specific requirements Utilize Blazor forms to efficiently collect user input and handle data validation Enhance your app with JavaScript logic, integrating it smoothly within your Blazor application Call RESTful APIs in Blazor, enabling seamless integration with external services Explore advanced identity and security techniques in Blazor ensuring robust authentication and authorization mechanisms Build reliable apps by implementing unit testing and effective error handling strategies Who this book is for This book is for existing .NET developers eager to leverage their C# skills to build single page applications without relying on JavaScript frameworks, as well as for JavaScript developers curious about Blazor's capabilities and its user-friendly approach to web development. Tech enthusiasts seeking an in-depth understanding of Blazor's inner workings will also find this guide useful for discovering and mastering Blazor's powerful and intuitive web development capabilities.